Association between physical housing conditions and pulmonary tuberculosis incidence: A cross-sectional study - Fera Meliyanti (School of Health Sciences Al-Ma'arif, 2026)
Background: Environmental determinants, particularly physical housing conditions, play an important role in facilitating the transmission of airborne infectious diseases such as tuberculosis. Poor ventilation, overcrowded living conditions, inadequate lighting, and substandard housing structures may increase the risk of pulmonary tuberculosis transmission within households and communities. Objective: This study aimed to analyze the association between physical housing conditions and the incidence of pulmonary tuberculosis in the working area of UPTD Puskesmas Pengaringan, Ogan Komering Ulu Regency, Indonesia. Methods: This study employed a descriptive analytical approach using a cross-sectional design. The study was conducted from October to December 2025 among suspected pulmonary tuberculosis patients attending UPTD Puskesmas Pengaringan. The study population consisted of 115 suspected tuberculosis patients, and a sample of 89 respondents was determined using the Slovin formula with a 5% margin of error. Participants were selected using purposive sampling based on predefined inclusion and exclusion criteria. Data were collected through structured interviews and direct observational measurements of housing conditions. Data analysis included univariate analysis to describe variable distributions and bivariate analysis using the Chi-square test with a significance level of α = 0.05 to examine associations between housing conditions and pulmonary tuberculosis incidence. Results: The results showed that 17 respondents (19.1%) were diagnosed with pulmonary tuberculosis. Bivariate analysis demonstrated significant associations between physical housing conditions and pulmonary tuberculosis incidence, including ventilation area (p = 0.026), residential density (p = 0.047), floor type (p = 0.021), and household lighting (p = 0.011). Respondents living in houses with inadequate ventilation, overcrowded conditions, inappropriate floor materials, and insufficient lighting had a higher proportion of pulmonary tuberculosis cases compared with those living in houses that met health standards. Conclusion: Physical housing conditions are significantly associated with pulmonary tuberculosis incidence in the study area. Improvements in household environmental conditions, including adequate ventilation, appropriate housing density, suitable floor materials, and sufficient lighting, are essential components of community-based tuberculosis prevention strategies.